WELCOMING IN PRIMARY HEALTH CARE IN THE PERCEPTION OF THE MULTIPROFESSIONAL TEAM - Fernandes Gomes, Rafael; Juliana Costa Diniz, Hellen; Alves Soares, Juliana; Paula Ferreira Maciel, Ana; Dias, Graziela; Gabriel de Jesus Rodrigues, Marcos; Mendes Cardoso, Jefferson; Carlos Pereira de Jesus, Ely; Ferreira de Carvalho Alves, Cândida; Barbosa Melo, Sirlene; Francisca de Souza, Zélia; Pereira Rocha, Marcirley; et al. (Estudos Avançados sobre Saúde e Natureza, 2024)
The objective of this study was to understand the perception of professionals who work in primary health care about user embracement. An integrative literature review was carried out, and articles retrieved from the Virtual Health Library, Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online and Online System for Search and Analysis of Medical Literature were analyzed from the descriptors reception, humanization and primary health care, from the Boolean operators. Studies indicate that the perception of professionals who work in primary health care about user embracement is often associated with the screening of an acute complaint, carried out at a specific time, especially in the morning shift, by a professional category that is also specific and will lead only to a medical consultation. A transformation in the training of health professionals is necessary, starting from academia and even after they are inserted in primary health care services.